APLIKASI INFORMASI TEMPAT WISATA JAWA TENGAH BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract- Central  Java  Province  as  one  of  the tourism destinations in Indonesia offers various tourist attractions both natural, cultural, tourist and man-made, which is very impressive as witnessing the wonders of the world such as Borobudor temple, Prambanan temple and a wide variety of interesting tour.  Most tourists come to  Central Java  to  see Javanese culture and tradition is still strong. Tourism for the Government of Central Java is one aspect to increase local revenue. One of the constraints faced by local government in terms of tourism development is the lack of an effective information system  for  tourists. System  development method used in this study is a prototype consisting of analysis, design, create prototypes, evaluation and improvement, results. System design using OOD consisting of use case diagrams and activity diagrams. Programming using Java programming and Android .The   end   result   of   this   research   is   the   application   of information-based tourist attractions in Central Java android can be used to display information sights consist of images, profiles and etymology tourist attractions in the form of text and location in google map form   Keywords - Places Of Interest, Central Java, Android, Prototype, Java